2017
DOI: 10.1016/j.fuel.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Continuous, self-sustaining smouldering destruction of simulated faeces

Abstract: A new approach for the rapid destruction of human waste using smouldering combustion is presented. Recently, self-sustaining smouldering combustion was shown to destroy the organic component of simulated human solid waste and dog faeces resulting in the sanitization of all pathogens using a batch process (Yermán et al., 2015). Here, a continuous smouldering process is demonstrated for the first time, allowing for a much smaller reactor size and much less energy input per mass of waste treated. The self-sustain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…moisture content, enthalpy of combustion, particle size), and whether it is required to add an inert porous material as bulk agent (Zanoni et al, 2019). Fabris et al (2017) described that an increment in the substrate destruction rate during the SSS can be achieved by increasing the Darcy air flow. However, this increase can also result in a drop of the smouldering temperature due to the effect of heat transfer between the combustion gases and the substrate in the reactor ).…”
Section: Introductionmentioning
confidence: 99%
“…moisture content, enthalpy of combustion, particle size), and whether it is required to add an inert porous material as bulk agent (Zanoni et al, 2019). Fabris et al (2017) described that an increment in the substrate destruction rate during the SSS can be achieved by increasing the Darcy air flow. However, this increase can also result in a drop of the smouldering temperature due to the effect of heat transfer between the combustion gases and the substrate in the reactor ).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not measure this temperature gradient, it has been reported that the temperature at the reactor centerline is ∼105 °C higher than that at the near-wall edge during the smoldering combustion of simulated feces. 19 To collect ashes at different locations, the second type of smoldering combustion experiments was conducted via packing the fuel-sand mixture in the smoldering column using six stainless steel meshes, with other conditions identical to those employed for the first type of experiments. After smoldering combustion, the meshes loaded with the mixture of sand and ashes were taken out from the reaction column layer-by-layer using two hooks.…”
Section: Methodsmentioning
confidence: 99%
“…Incineration usually involves complete decomposition of organic matter by means of oxidation to carbon dioxide. Smoulder combustion (Yerm an et al, 2015(Yerm an et al, , 2017Fabris et al, 2017) also aims at complete decomposition of organic matter but can be designed to yield pyrolysis products such as biocrude. Pyrolysis and HTL have been investigated with recovery of both nutrients and energy in mind, while the other processes have typically been targeted primarily towards recovering carbon in the form of charcoal or energy carriers.…”
Section: Thermal Decompositionmentioning
confidence: 99%